2010
DOI: 10.1103/physreva.81.053851
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of an asymmetric Gaussian beam in a nonlinear absorbing medium

Abstract: Propagation of an asymmetric Gaussian beam in a cubic-quintic absorbing medium is analyzed and compared with that of a symmetric beam in both lossless and lossy media. A "collective variable approach" technique, based on trial functions, is used for solution of the general nonlinear Schrödinger equation. Using this variational approach, we investigate the self-focusing and breathing of an intense asymmetric Gaussian beam, taking into account both linear and nonlinear absorption. For a lossless medium, we defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
21
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 18 publications
1
21
0
Order By: Relevance
“…This is in contrast to the cubic-quintic medium where the beating is always of the same type [12]. The refractive index n can be written as n 2 = n 2 0 + n 0 n 2 |E| 2 1 + n 0 n 2 |E| 2 / n 2 sat − n 2…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This is in contrast to the cubic-quintic medium where the beating is always of the same type [12]. The refractive index n can be written as n 2 = n 2 0 + n 0 n 2 |E| 2 1 + n 0 n 2 |E| 2 / n 2 sat − n 2…”
mentioning
confidence: 99%
“…However, considerable physical insight can be gained if the GNLSE is solved approximately in a semianalytical fashion [1,2] using the "collective variable approach" (CVA) [10,11] for conservative systems. The CVA technique is based on a trial function, such as a Gaussian function, with a finite number of variables, which is usually a function of the propagation coordinate that evolves subject to the constraints of the system.The CVA technique was recently used to investigate propagation of an asymmetric Gaussian beam in a lossy cubicquintic medium [12], which is characterized by competition between a self-focusing χ (3) Kerr nonlinearity and a selfdefocusing χ (5) nonlinearity. It was shown that there are two main regions of behavior, periodic and non-periodic.…”
mentioning
confidence: 99%
“…Taking into account the permittivity profile defined in Eq. (1), one can notice that the wave number in nonlinear dissipative/gain media is complex-valued: [5][6][7]), one can notice that despite the fact that the wave number k defined in Eq. (4) is, in general, a complex-valued quantity, the propagation constant ( 0, )…”
Section: Xymentioning
confidence: 99%
“…Nowadays, there are many papers concerning nonlinear optics discussing the joint influence of linear and nonlinear absorption processes (embracing twophoton absorption phenomenon) on the self-focusing of a Gaussian light beam. For instance, a number of numerical examples describing and discussing this problem are presented in the paper [6]. However, in the author's opinion it is very difficult to capture, in fact, the role of nonlinear absorption in a nonlinear self-focusing medium when linear dissipation dominates over nonlinear, which is demonstrated by the results in paper [6].…”
Section: Xymentioning
confidence: 99%
See 1 more Smart Citation